tweeDe - Rehbein, Ines; Ruppenhofer, Josef; Do, Bich-Ngoc (Universität, 2020)
A German UD Twitter treebank, with >12,000 tokens from 519 tweets, annotated in the Universal Dependencies framework
Production date: 2019
Kind of data: Archived tab-separated text (CoNLL-U)
Gesehen am 04.05.2020
Keywords: Forschungsdaten; Datenbank